American-sponsored public schools in colonial Kabikolan, 1901-1921 - Totanes, Stephen Henry S. (2002)
On August 23, 1901, with the arrival in Manila of the U.S. Army transport, U.S.S. Thomas, carrying 540 or so American teachers who would be deployed to the various provinces, the efforts of the Philippine Commission to establish a public school system all over the Philippines using English as a medium of instruction began in earnest. These pioneer teachers, known as the "Thomasites," laid the foundations for the establishment of public schools not only in Manila and the provincial capitals but also in far-flung municipalities. These efforts have been documented in various publications and were recently commemorated with a centennial conference sponsored by the American Studies Association of the Philippines (ASAP) and the Thomasites Centennial Project of the United States Embassy (Pecson and Racelis 1959; Racelis and Ick 2001; To Islands Far Away 2001). This paper hopes to add to a better understanding of this undertaking by providing an overview of the effort to establish primary and secondary public schools by these American teachers in the first two decades of American colonial rule particularly in the region of Kabikolan. Given the geographical characteristics of the region, an area comprising over 17,000 square kilometers and home to a little over half a million inhabitants spread over three major provinces in 1901, the attempt to provide an opportunity for education for young Bikolanos at that time can be seen either as an extremely ambitious project or a truly remarkable and highly laudable feat.